A contribution for the study of RTM effect in height anomalies at two future IHRS stations in Brazil using different approaches, harmonic correction, and global density model - Rodrigues Tiago Lima (Journal of Geodetic Science, 2022)
The high-frequency effects of the gravity field can be obtained from residual terrain modeling (RTM) technique. However, for the International height reference system (IHRS), this is an open problem. Over the last decades, various approaches have been proposed for the practical solution of Newton’s Integral, such as point-mass, tesseroid, prism, and polyhedron. Harmonic correction (HC) and the use of more realistic mass density values have also been studied. In this work, in order to calculate RTM height anomalies at BRAZ and PPTE IHRS future stations in Brazil, such approaches and issues have been evaluated. Density values have been obtained from CRUST 1.0 global model. For the HC, the traditional mass condensation technique and Poisson’s equation have been used. The resulting values proposed by different approaches are very close to each other, with differences at the submillimeter-level. The RTM height anomaly values reached 1.5 and 1.4 mm at the BRAZ and PPTE stations, respectively. HC at BRAZ station can be disregarded without prejudice since its order of magnitude was 10−5 m. The use of CRUST 1.0 density values has proposed slight improvements of 0.8 and 0. 4 mm at BRAZ and PPTE station, respectively, in relation to the use of Harkness constant density value.